2019
DOI: 10.1007/s00299-019-02431-z
|View full text |Cite
|
Sign up to set email alerts
|

Production of recombinant proteins through sequestration in chloroplasts: a strategy based on nuclear transformation and post-translational protein import

Abstract: Recently, plants have emerged as a lucrative alternative system for the production of recombinant proteins, as recombinant proteins produced in plants are safer and cheaper than those produced in bacteria and animal cell-based production systems. To obtain high yields in plants, recombinant proteins are produced in chloroplasts using different strategies. The first strategy is based on chloroplast transformation, followed by gene expression and translation in chloroplasts. This has proven to be a powerful appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 85 publications
(100 reference statements)
0
9
0
Order By: Relevance
“…More recent work in N. benthamiana has demonstrated transient expression of both receptor binding and S1 domains of the SARS-CoV-2 spike protein and successful downstream application to immunoassays [19,20]. The main drawback of plant-based expression systems is that they have low biomass productivity compared to microbial systems and have laborious and technically demanding transformation methods that can require months to achieve if stable integration is required [21].…”
Section: Introductionmentioning
confidence: 99%
“…More recent work in N. benthamiana has demonstrated transient expression of both receptor binding and S1 domains of the SARS-CoV-2 spike protein and successful downstream application to immunoassays [19,20]. The main drawback of plant-based expression systems is that they have low biomass productivity compared to microbial systems and have laborious and technically demanding transformation methods that can require months to achieve if stable integration is required [21].…”
Section: Introductionmentioning
confidence: 99%
“…The membrane (M) and nucleocapsid (N) proteins of SARS were expressed transiently in Nicotiana benthamiana, with the N protein demonstrating antibody recognition in convalescent serum samples (Demurtas et al, 2016). The main drawback of plant-based expression systems is that they have low biomass productivity compared to microbial systems, and have laborious and technically demanding transformation methods that can require months to achieve (Muthamilselvan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Third, plants are almost free of endotoxins such as lipopolysaccharides, which are abundant in bacterial cells. Further, the conditions for plant growth are much less affected by microorganisms that are detrimental to mammalian cell cultures (Buyel et al, 2017 ; Moon et al, 2019 ; Muthamilselvan et al, 2019 ; Knodler and Buyel, 2021 ; Schillberg and Finnern, 2021 ). In addition, previous studies indicated that various useful proteins of different origins, such as bacteria, bacteriophage, animals, and red algae, remained functional when produced in tobacco ( Nicotiana benthamiana ) (Garvey et al, 2013 ; Islam et al, 2019 , 2020 ; Kumari et al, 2020 ; Razzak et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to enhance the production of foreign proteins, several sequences such as 5′-untranslated region (UTR) and HSP transcriptional terminator have been formulated and incorporated into plant expression vectors (Nagaya et al, 2010 ; Kim et al, 2014 ; Islam et al, 2019 ). To avoid the proteolytic degradation of target proteins in the cytosol, expressed proteins can be sequestered to subcellular organelles such as endoplasmic reticulum (ER) or chloroplasts by incorporating organellar targeting signals that are proteolytically removed by organellar peptidase after organellar targeting of proteins (Lee and Hwang, 2018 ; Islam et al, 2019 ; Muthamilselvan et al, 2019 ; Margolin et al, 2020b ). ER is an organelle in which several posttranslational modifications such as glycosylation or disulfide bond formation occur, thereby contributing to the functionality of produced proteins (Margolin et al, 2018 , 2020a ).…”
Section: Introductionmentioning
confidence: 99%